Conventional and novel body temperature measurement during rest and exercise induced hyperthermia. (January 2017) - Towey, Colin; Easton, Chris; Simpson, Robert; Pedlar, Charles
Abstract: Despite technological advances in thermal sensory equipment, few core temperature (TCORE ) measurement techniques have met the established validity criteria in exercise science. Additionally, there is debate as to what method serves as the most practically viable, yet upholds the proposed measurement accuracy. This study assessed the accuracy of current and novel TCORE measurement techniques in comparison to rectal temperature (TREC ) as a reference standard. Fifteen well-trained subjects (11 male, 4 female) completed 60 min of exercise at an intensity equating to the lactate threshold; measured via a discontinuous exercise test. TREC was significantly elevated from resting values (37.2±0.3 °C) at the end of moderate intensity exercise (39.6±0.04 °C; P=0.001). Intestinal telemetric pill (TPILL ) temperature and temporal artery temperature (TTEM ) did not differ significantly from TREC at rest or during exercise (P>0.05). However, aural canal temperature (TAUR ) and thermal imaging temperature (TIMA ) were both significantly lower than TREC (P<0.05). Bland Altman analysis revealed only TPILL was within acceptable limits of agreement (mean bias; 0.04 °C), while TTEM, TAUR and TIMA demonstrated mean bias values outside of the acceptable range (>0.27 °C). Against TREC, these results support the use of TPILL over all other techniques as a valid measure of TCORE at rest and during exercise induced hyperthermia. Novel findings illustrate that TIMA (when measured at the inner eye canthus) shows poor agreement to TREC during rest and exercise, which is similar to other 'surface' measures. Highlights: Core temperature measurements were taken throughout rest and 60 min exercise induced hyperthermia, and their agreement with rectal temperature as a reference standard was assessed. Findings in relation to conventional measures of telemetric pill, aural canal and temporal artery temperature highlight that only the telemetric pill showed acceptable limits of agreement when compared to rectal temperature. Novel findings highlighted that thermal imaging showed very poor agreement with rectal temperature when measuring the heat radiation from the inner eye canthus. Further research is required to robustly determine which core temperature measure(s) is the most fit for purpose for monitoring the hyperthermic athlete.